2017
DOI: 10.1186/s12877-017-0425-4
|View full text |Cite
|
Sign up to set email alerts
|

How does washing without water perform compared to the traditional bed bath: a systematic review

Abstract: BackgroundFor immobile patients, a body wash in bed is sometimes the only bathing option. Traditionally, the bed bath is performed with water and soap. However, alternatives are increasingly used in health care. Washing without water is one such alternative that has been claimed to offer several advantages, such as improved hygiene and skin condition. This systematic review aims to provide a comprehensive overview of the evidence on outcomes of the washing without water concept compared to the traditional bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 34 publications
1
45
0
4
Order By: Relevance
“…We think, that patient involvement are important here, and the nurses should be aware of giving the patients information about the two bath types, so they are more capable of making their own choice. In other studies it is shown, that the older inhabitants gets more help with their personal hygiene where disposable bath are preferred in patients homes and in nursing homes [9,10].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We think, that patient involvement are important here, and the nurses should be aware of giving the patients information about the two bath types, so they are more capable of making their own choice. In other studies it is shown, that the older inhabitants gets more help with their personal hygiene where disposable bath are preferred in patients homes and in nursing homes [9,10].…”
Section: Discussionmentioning
confidence: 91%
“…Since the disposable bath was invented in 1994, there have been a number of research efforts into the product, which have been published [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The research comes from a number of countries UK, US, Nederland and Denmark.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recently published systematic review concluded there is no research showing evidence of superior quality between BB and CBB, recommending future research on BB, including attention to costs, hygiene, and results related to the interested parties, such as the experiences and perceptions of patients, their families, and the nursing staff. (21)(22)(23) Thus, this study can be considered a national and international innovation for providing scientific evidence for hospital nurses and administrators to make safe decisions on the adoption of BBs, as well as for flagging the need for nursing professionals to conduct studies to re-evaluate the CBB procedure propagated through nursing textbooks, and finally as a method of evaluating the effectiveness of other BB-like products in the market.…”
Section: Discussionmentioning
confidence: 99%
“…Results of a systematic review showed washing without water is a worthy alternative for the traditional bed bath with water and soap. However, the number of studies on washing without water is limited and evidence for patient-related variables, such as physical or emotional comfort is lacking [7].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that the duration of the bed bath with washing without water is shorter compared to the traditional bed bath with water and soap. The reduced time consumption as well as the convenience of the concept have been reported to be reasons for nurses to prefer washing without water to the traditional bed bath [7]. In addition, washing without water is argued to be less physically burdensome for nurses.…”
mentioning
confidence: 99%